Synthesis and characterization of magnesium hydroxide nanoparticles via sol-gel - Sami, Suseela (Malaysian NANO-An International Journal, 2022)
The magnesium hydroxide (Mg (OH)2 nanoparticles (NPs) were prepared using the sol-gel method and presented its results in this work. Various characterization methods have been used to confirm the successful preparation of Mg (OH)2 NPs. The XRD analysis exhibited the hexagonal structure of the sample. FT-IR spectrum revealed the presence of metal-oxygen stretching of prepared magnesium hydroxide NPs. The SEM analysis shows that the synthesized Mg (OH)2 NPs were clustered with a rough stacked surface. From the absorption peak obtained through UV-Vis spectroscopy, the bandgap energy of Mg (OH)2 NPs was calculated as 2.70 eV.